Підхід цифрового криміналістичного аналізу повідомлень електронної пошти - Шедін, Д. А. (ХНУРЕ, 2023)
The increasing prevalence of cyber threats and phishing attacks in our daily lives has made it more crucial than ever to be vigilant about the emails we receive. Even though email services come with built-in security features, they are not always reliable. Analyzing the sender’s domain and email headers is an additional way that helps clients quickly identify potential vulnerabilities and take appropriate action. The currently available external tools require more effort from the user to collect this information in one place and do not always show data in an easy-to-read format. My user-friendly and simple-to-install browser extension is the solution that allows to get this information without leaving the email client